Development of Hybrid Model of STATCOM - Ufa R. A. Ruslan Alexandrovich; Vasilev A. S. Alexey Sergeevich; Gusev A. S. Alexander Sergeevich; Suvorov A. A. Aleksey Aleksandrovich (Mechatronics, electrical engineering and power electronics, 2016)
Title screen